The Influence Of Social Media Marketing, Brand Loyalty, Brand Trust On Value Co-Creation In The Aerostreet Brand - Mahendra, Irvan Ady; Ridanasti, Erlita (Cita konsultindo, 2024)
This study aims to examine the influence of Social Media Marketing, Brand Loyalty, and Brand Trust on Value Co-Creation for the AeroStreet brand, using a quantitative approach. Data were collected through questionnaires distributed to 127 respondents who are users of AeroStreet products, particularly footwear. The data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. A pilot test was conducted with an initial sample of 30 using SPSS. The results of the study indicate that Social Media Marketing positively influences Brand Trust and Brand Loyalty, but does not have a significant effect on Value Co-Creation. Furthermore, Brand Trust and Brand Loyalty both have a positive impact on Value Co-Creation.